2017
DOI: 10.1002/14651858.cd005070.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant luteinizing hormone (rLH) and recombinant follicle stimulating hormone (rFSH) for ovarian stimulation in IVF/ICSI cycles

Abstract: Recombinant luteinizing hormone (rLH) and recombinant follicle stimulating hormone (rFSH) for ovarian stimulation in IVF/ICSI cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 59 publications
1
64
0
3
Order By: Relevance
“…[21,22]. The updated Cochrane review showed no clear evidence of a difference between rLH combined with rFSH and rFSH alone in live birth rates in spite of more ongoing pregnancies under LH supplementation, in which the benefits appeared to be more evident for low responders [23]. Hence, we don't propose the long-acting FSH plus MPA regimen in low responders.…”
Section: Resultsmentioning
confidence: 92%
“…[21,22]. The updated Cochrane review showed no clear evidence of a difference between rLH combined with rFSH and rFSH alone in live birth rates in spite of more ongoing pregnancies under LH supplementation, in which the benefits appeared to be more evident for low responders [23]. Hence, we don't propose the long-acting FSH plus MPA regimen in low responders.…”
Section: Resultsmentioning
confidence: 92%
“…A large proportion of patients receiving ART treatment (43.3% in one study) would fulfill the criteria for suboptimal response or expected suboptimal response [23]. Based on recent meta-analyses, there is evidence that suboptimal responders and potentially other patient populations are likely to benefit from r-hLH supplementation [45][46][47][48][49] with respect to implantation, pregnancy, and live birth rates.…”
Section: Ovulatory Women (Including Women With Unexplained Infertilitmentioning
confidence: 99%
“…Taking LBR as a surrogate marker of embryo euploidy, in a Cochrane review of 36 RCTs (8125 women) there was insufficient evidence to determine whether there was a difference between rLH combined with rFSH vs rFSH alone in LBR (OR: 1.32, 95% CI: 0.85-2.06; n = 499; studies = 4; I 2 = 63%, very low-quality evidence) (Mochtar et al 2017). The most recent systematic review assessing the role of rLH supplementation in COS for ART in specific subgroups of patients was published by Alviggi et al (2018).…”
Section: Lh Supplementationmentioning
confidence: 99%